PENGARUH ANGKA HARAPAN LAMA SEKOLAH PEREMPUAN TERHADAP JUMLAH PENDUDUK MISKIN DI INDONESIA DALAM PERSPEKTIF MANAJEMEN SUMBER DAYA MANUSIA - Desy Rahmawati; Achmad Efendi; Rinda Sandayani Karhab (Universitas Sarjanawiyata Tamansiswa, 2026)
The purpose of this study is to analyze the effect of women's life expectancy on the total number of poor people in Indonesia from a human resource management perspective. Female education is seen as a strategic investment in human resources that can improve skills, productivity, and economic decision-making capacity, thereby contributing to poverty reduction. A quantitative approach was applied in this study, accompanied by the use of secondary data in the form of time series obtained from Statistics Indonesia (BPS) during the period 2014–2024. The sampling technique used is saturated sampling, with simple linear regression analysis. Data analysis includes descriptive statistics, classical assumption tests, hypothesis testing using t-tests, and the coefficient of determination (R²) processed using SPSS version 25. This study found that the average years of education of women had a significant negative effect on the total poor population in Indonesia. This finding indicates that improving women's education contributes to encourage improvements in the quality of human resources and reduce poverty levels in the society. However, poverty is also influenced by other structural and economic factors, so the development of women's education needs to be supported by job creation and inclusive economic policies.